The Forzon and Vacum Space Energy: A Novel Perspectives - Acosta , D. S. (Fundamental Research and Application of Physical Science Vol. 4, 2023)
The purpose of this work was to explain the way in which the Forzon obtains its energy from space and in which form this energy is found in the vacuum space in order for the Forzon to use it; while also being the source of other manifestations, such as the universe expansion, the dark matter, dark energy, gravitation and the electromagnetic fields. The Forzon theory is consistent with its calculations and furthermore one of its prediction, related to the accumulation of kinetic energy in agrupacion of surface areas of unidirectional forzons has been experimentally documented in highly energetic protons observed in the big European particle accelerator LHC. All of this leads to a model of a fluid universe in which time is the foundation of matter and energy, as well as the space evacuator. OIS space, i.e. the model of tense space evacuated by time surface areas marks a possible scientific pathway towards the complete understanding of dark matter, also known as vacuum space and general dynamic of the universe.